Arthrodesis of the elbow in three cats - Moak, P. C.; Lewis, D. D.; Roe, S. C.; de Haan, J. J. (Veterinary and Comparative Orthopaedics and Traumatology, 2000)
Severe disorders of the elbow in three cats were treated with arthrodesis. Fusion for two cats was achieved with bone plate application on the caudal aspect of the elbow. A modified trans-articular external skeletal fixator was used for arthrodesis of one elbow. All three elbows progressed to arthrodesis. One cat fractured the radius and ulna distal to the plate following arthrodesis; the forelimb was eventually amputated following additional complications. The remaining two cats were intermittently weight-bearing on the involved forelimb with marked circumduction of the limb during the swing phase of the stride, but the owners perceived their cats to be free of pain. Arthrodesis of the elbow is an alternative to amputation in order to achieve pain relief and limb salvage following severe elbow disorders in cats. However, limb function in these three cats was severely compromised.Arthrodesis has been described as a salvage procedure for orthopaedic disorders of the elbow in dogs. This report describes the indications, surgical techniques, and clinical results of elbow arthrodesis in three cats.
Keywords: Arthrodesis; elbow; cat